Growth and derived life-history characteristics of the Brazilian electric ray Narcine brasiliensis - Rolim, Fernanda A. [UNESP]; Siders, Zachary A.; Caltabellotta, Fabio P.; Rotundo, Matheus M.; Vaske-Júnior, Teodoro [UNESP] (Wiley, 2020)
The majority of batoids are listed as Threatened (20.4%) or Data Deficient (41%) by the IUCN Red List. A key challenge to assessing Data-Deficient species is obtaining estimates of key life-history characteristics. Here, a Bayesian approach was used to estimate derived life-history characteristics from a growth model applied to the Data-Deficient Brazilian electric ray Narcine brasiliensis. The age of 170 specimens (107 females, 63 males) was estimated from vertebral centra, and total length, disc width, total weight and birth size were used in a joint estimation of sex-specific length-weight models and two-dimensional von Bertalanffy growth models. Estimates of age at length zero, age at maturity, longevity and mortality at age were derived simultaneously. The Bayesian joint modelling approach was robust to small sample sizes by adding a likelihood to constrain L0 and sharing parameters, such as Brody growth coefficient between length measurements. The median growth parameter estimates were a shared L0 = 38.8 mm, female L∞ = 515 mm, K = 0.125 and male L∞ = 387 mm, K = 0.194. Age at maturity was estimated to be 7.40–7.49 years for females and 4.45–4.47 years for males, whereas longevity was 22.5–22.6 years for females and 14.2 years for males depending on length measurement. Age-1 natural mortality was estimated to be 0.199–0.207 for females and 0.211–0.213 for males. The derived life-history characteristics indicate N. brasiliensis is earlier maturing, but slower growing relative to other Torpediniformes. These characteristics along with the species’ endemism to southern Brazil and high by-catch rates indicate that one of the IUCN Red List threatened categories may be more appropriate for the currently Data-Deficient status. The Bayesian approach used for N. brasiliensis can prove useful for utilizing limited age-growth data in other Data-Deficient batoid species to inform necessary life characteristics for conservation and management.
Keywords: age and growth; Batoidea; Bayesian; life history; Narcinidae